2021
DOI: 10.1111/and.14343
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circ_0062019 exerts oncogenic properties in prostate cancer via mediating miR‐1253/NRBP1 axis

Abstract: ing to 2018 statistics, the incidence of prostate cancer continues to rise, ranking fifth among male cancers (Bray et al., 2018). Despite PCa treatment has made significant progress, advanced PCa still imposes a huge social and economic burden (Cassell et al., 2019).Consequently, exploring new potential biomarkers is essential to discover new treatment strategies for prostate cancer. Circular RNAs (circRNAs) are single-stranded endogenous molecules constructed by back-splicing (Li et al., 2020). CircRNAs with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…A study found that circ0062019 is highly expressed in PCa tissue and multiple PCa cell lines [ 173 ]. Knockdown of circ0062019 inhibits the proliferation and the cell cycle of PCa cells, promoting cellular apoptosis.…”
Section: Expression and Biological Function Of Circrnas In Urinary Sy...mentioning
confidence: 99%
“…A study found that circ0062019 is highly expressed in PCa tissue and multiple PCa cell lines [ 173 ]. Knockdown of circ0062019 inhibits the proliferation and the cell cycle of PCa cells, promoting cellular apoptosis.…”
Section: Expression and Biological Function Of Circrnas In Urinary Sy...mentioning
confidence: 99%
“…Therefore, the circRNA/EMT axis is a regulator of prostate cancer invasion. The delineation of molecular pathways that can be targeted for treatment of this malignant disease warrants further research [ 217 , 218 ].…”
Section: Circrna/emt Axis In Different Cancersmentioning
confidence: 99%